Pengembangan Media Perdalstik Pada Materi Perkalian Kelas III SD - Pirda Amalia (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
The development of this research was motivated by the problems that were obtained by the lack of variety of learning media in the field of mathematics lessons in class III, especially in multiplication, students only did a sketch using paper to find the results of multiplication problems, but students' interest in discussing multiplication in the field of mathematics lessons in class III SD can be said interest, it's just that there hasn't been any learning media creation. This research aims to Develop a mathematics learning media in the form of perdalstik (multiplication in sticks) to enhance students' learning experiences in discussing multiplication for class III SDN Gunung Picung 08 Bogor Regency. The development of Perdalstic learning media research on multiplication material for class III at SDN Gunung Picung 08, researchers used a development approach or what is known as Research and Development (R&D) with a research model that is obtaining products that are needs analysis, with the ADDIE model but only up to the development stage , it is necessary to study learning media, namely Perdalstik (multiplication in sticks) which aims to foster the learning experience of third grade elementary school students. The research assessment was conducted with 2 experts, namely the media and material validators. The perdalstic media (multiplication in sticks) gets a score of (1) from media experts getting a score of 100% (2) and material experts getting a score of 100%. So it proves from the two assessments that the learning media is considered to be in the